Factors that encourage women to be an SME entrepreneur in PKNS Complex Shah Alam / Muhammad Azhar Abd Mulop - Abd Mulop, Muhammad Azhar (2014)
The purpose of this research is to study on the Factors That Encourage Women to be an SME Entrepreneur in PKNS Complex Shah Alam. There are four factors that encourage women to be an SME entrepreneur in PKNS Complex Shah Alam. Those factors are exclusion / inequality, education, information and communication technology (ICT) and family support. The researcher set several objectives to be achieved in carrying out this study. In collecting data, the researcher used both primary and secondary data. The questionnaire was made to measure the reliability of the question that was distributed to all the respondents. Several techniques were used to analyze the data. The researcher studied the demographic profiles of the respondent and the researcher also made the frequency analysis on every variable. Then, mean analysis was made on the entire identified variable. Lastly, correlation analysis and regression analysis was made to determine the relationship between independent variables and dependent variable. From the findings, the reliability tests for all variables are acceptable for this research. The independent variables which are exclusion / inequality, education, information and communication technology (ICT) and family support are significant. Two variables have positive relationships which are exclusion / inequality and family support while another two variables have negative relationships which are education and information and communication technology (ICT). The researcher made a conclusion about the study and several recommendations were put forward.